The impact of BMI on life expectancy in Portugal (Acta Scientiarum. Health Sciences, 2024)
The overweight represents a serious public health problem in Portugal, with a prevalence that exceeds 50%. Obesity-related diseases constitute the health system's main causes of death and economic issues. Despite this, there is no consensus on the relationship between the Body Mass Index (BMI) and the risk of early mortality. In this context, assessing the impact of the average BMI on life expectancy in Portugal is important. A retrospective cross-sectional observational study was carried out using an Autoregressive Distributed Lag model. The dependent variable is life expectancy at birth, expressed in the total years obtained from the World Development Indicators (WDI). The independent variables are: (i) the average BMI of the population (calculated based on the average male and female BMI obtained from Our World in Data); and (ii) the total population obtained from the WDI. The population's mean BMI variable limited the study's time horizon, comprising annual statistical data from 1975 to 2016. The increase in BMI negatively affects the life expectancy of the Portuguese population in the short term. A 1% variation in BMI reflects a 1.98% reduction in life expectancy. The result was statistically significant at 1%, and the p-value was 0.0001. In the long term, there was no statistically significant effect of the mean BMI on the population's life expectancy. Also, in the long term, population growth has a positive and statistically significant effect on life expectancy. Although there is no consensus in the literature that BMI is associated with increased mortality, the results obtained through this model captured this trend in Portugal in the short term. Therefore, promoting life expectancy by improving the Portuguese's health and quality of life is necessary. The adoption of measures that favor the recovery or maintenance of normal weight is essential.